2010
DOI: 10.1016/j.canlet.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant doses of chemotherapy agents reversibly block formation of glioblastoma neurospheres

Abstract: Glioblastoma patients have a poor prognosis, even after surgery, radiotherapy, and chemotherapy with temozolomide or 1,3-bis(2-chloroethy)-1-nitrosourea. We developed an in vitro recovery model using neurosphere cultures to analyze the efficacy of chemotherapy treatments, and tested whether glioblastoma neurosphere initiating cells are resistant. Concentrations of chemotherapy drugs that inhibit neurosphere formation are similar to clinically relevant doses. Some lines underwent a transient cell cycle arrest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…The neurosphere recovery assay provides a quantitative cell culture assay to test the efficacy of drug combinations at inhibiting repopulation. We demonstrated that temozolomide drastically diminished initial neurosphere formation in many glioma cultures; however, these cultures eventually recovered and formed a robust number of secondary neurospheres (Mihaliak et al, 2010). The ability of temozolomide treated neurospheres to recover and repopulate the culture suggests that some cells undergo a transient cell cycle arrest, allowing them to evade cell death and eventually resume proliferation.…”
Section: Chemoresistance and Radioresistancementioning
confidence: 86%
See 3 more Smart Citations
“…The neurosphere recovery assay provides a quantitative cell culture assay to test the efficacy of drug combinations at inhibiting repopulation. We demonstrated that temozolomide drastically diminished initial neurosphere formation in many glioma cultures; however, these cultures eventually recovered and formed a robust number of secondary neurospheres (Mihaliak et al, 2010). The ability of temozolomide treated neurospheres to recover and repopulate the culture suggests that some cells undergo a transient cell cycle arrest, allowing them to evade cell death and eventually resume proliferation.…”
Section: Chemoresistance and Radioresistancementioning
confidence: 86%
“…Several groups have proposed that cancer stem cells readily assume a quiescent state and later, following DNA repair, repopulate the tumor (Mellor et al, 2005;Scopelliti et al, 2009). Our laboratory recently demonstrated that even low doses of temozolomide can induce quiescence followed by a robust recovery of the culture (Mihaliak et al, 2010). The neurosphere recovery assay provides a quantitative cell culture assay to test the efficacy of drug combinations at inhibiting repopulation.…”
Section: Chemoresistance and Radioresistancementioning
confidence: 99%
See 2 more Smart Citations
“…Further publications addressing cancers of breast, brain, colon, lung, skin, and pancreas followed. The main focus in these studies was on the analysis of growth inhibition [28,29], inhibition of migration and invasion [30], induction of cell cycle arrest [31,32] and induction of apoptosis in a dose-dependent manner [33,34], [35][36][37][38][39]. Recent experiments on melanoma verified the induction of apoptosis with high CAP treatment times, whereas low treatment times were able to induce senescence [40].…”
Section: State Of the Art/tumor Treatment With Capmentioning
confidence: 99%